2019
DOI: 10.3390/su11030719
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Education for Sustainable Development at an Early Stage: Cornerstones and Pedagogical Approaches for Teacher Professional Development

Abstract: During recent decades, education for sustainable development (ESD) has been under the scope of the international community, but research in ESD for early childhood education (ECE) is still scarce. This article proposes a procedural framework for the implementation of teacher professional development opportunities in the area. During the first phase, we undertook a systematic review of peer-reviewed articles on ESD for ECE (n = 30). After an expert committee revision of the articles reviewed, three cornerstones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 47 publications
3
71
0
8
Order By: Relevance
“…Bascopé et al [105], in their systematics literature review, found that the term 'community' is used in various ways depending on the context, while it is not clearly defined. It may refer to the closer educational community (e.g., parents and neighborhood) or the local place in a more general sense.…”
Section: Community Involvementmentioning
confidence: 99%
See 2 more Smart Citations
“…Bascopé et al [105], in their systematics literature review, found that the term 'community' is used in various ways depending on the context, while it is not clearly defined. It may refer to the closer educational community (e.g., parents and neighborhood) or the local place in a more general sense.…”
Section: Community Involvementmentioning
confidence: 99%
“…Similarly, in their literature review, Bascopé et al (2018) revealed three forms of community involvement: (a) learning from and about their own community through participating in life in community and communicating with community members; (b) acting upon issues in the community as an attempt to solve SD-related problems and (c) co-learning and acting with the community, means that community members (e.g., parents) cooperate with students to solve SD-related problems while they have themselves the opportunity to learn by taking part in this process. Bascopé et al [105] pinpoint that these three forms of community involvement do not exclude but complete each other.…”
Section: Community Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the research carried out has evolved towards a transdisciplinary vision that attempts to explain the emerging theme from pedagogical approaches focused on the professional development of teachers on the formation of a sustainable citizenship from early ages, to higher studies [30,31], technology-mediated learning for a sustainable education [32,33], as well as the imminent need for teacher training to integrate skills related to education for sustainability, considering both individual differences and the common good of the community [34].…”
Section: Discussionmentioning
confidence: 99%
“…Everyone has the right to acquire and understand which skills allow full participation in society and also help people choose appropriate fields of study [15]. Its aim is to provide a standard framework for both research and practice to support sustainable mathematical competences [16,17].…”
Section: Introductionmentioning
confidence: 99%